Solve the equation:

`3\left(3x+4\right)-6x=-9`

1 answer

To solve the equation:

First, distribute the 3 to both terms inside the parentheses:

9x + 12 - 6x = -9

Combine like terms by subtracting 6x from 9x:

3x + 12 = -9

Next, subtract 12 from both sides of the equation:

3x = -21

Finally, divide both sides of the equation by 3 to solve for x:

x = -21/3

Therefore, the solution is x = -7.
Similar Questions
  1. You need to solve this equation for x: ax-7=26Which equation would be best first step you could make to solve the equation? (1
    1. answers icon 1 answer
  2. You need to solve this equation for x: ax−7=26Which would be the best first step you could make to solve the equation? (1
    1. answers icon 5 answers
  3. ou need to solve this equation for x: ax−7=26Which would be the best first step you could make to solve the equation? (1
    1. answers icon 1 answer
  4. You need to solve this equation for x: ax−7=26Which would be the best first step you could make to solve the equation? (1
    1. answers icon 22 answers
more similar questions